1999
DOI: 10.1159/000012361
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunctions in Bipolar Disorder: Evidence of Neuropsychological Disturbances

Abstract: Although cognitive dysfunctions in psychosis have classically been associated with schizophrenia, there is clinical evidence that some bipolar patients show cognitive disturbances either during acute phases or in remission periods. The authors critically review the data on cognitive impairment in bipolar disorder. The main computerized databases (Medline, Psychological Abstracts, Current Contents) have been consulted crossing the terms ‘cognitive deficits’, ‘neuropsychology’, ‘intellectual impairment’, ‘mania’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
139
1
11

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(163 citation statements)
references
References 107 publications
(125 reference statements)
12
139
1
11
Order By: Relevance
“…Cognitive impairments have previously been described in FH and also in manic, depressed, and euthymic BD patients (Sobczak et al, 2002c;Rossi et al, 2000;Martinez-Aran et al, 2000;Ferrier et al, 1999;Murphy et al, 1999;Rubinsztein et al, 2000). The cognitive deficits in BD may be partially explained by abnormalities in functional brain structures and/or metabolism (Stoll et al, 2000;Manji et al, 2000;van Gorp et al, 1999;Coffman et al, 1990).…”
Section: Discussionmentioning
confidence: 89%
“…Cognitive impairments have previously been described in FH and also in manic, depressed, and euthymic BD patients (Sobczak et al, 2002c;Rossi et al, 2000;Martinez-Aran et al, 2000;Ferrier et al, 1999;Murphy et al, 1999;Rubinsztein et al, 2000). The cognitive deficits in BD may be partially explained by abnormalities in functional brain structures and/or metabolism (Stoll et al, 2000;Manji et al, 2000;van Gorp et al, 1999;Coffman et al, 1990).…”
Section: Discussionmentioning
confidence: 89%
“…The first-line mood-stabilizing treatments include lithium, divalproex, olanzapine, and lamotrigine (the latter mainly for those with mild manias) (Yatham et al, 2009). BD has also been coupled to cognitive impairment including reduced abilities in executive function and verbal memory (Martinez-Aran et al, 2000;Zarate et al, 2000;Martinez-Aran et al, 2005;Robinson et al, 2006;Sanchez-Moreno et al, 2009;Palsson et al, 2013). Structural imaging studies have suggested that the decline in cognitive function is associated with morphological abnormalities of the brain (Altshuler et al, 1995;McDonald et al, 2004;Kempton et al, 2008;Konarski et al, 2008), and that the number of manic episodes is associated with decreased gray matter in dorsolateral prefrontal cortex (Ekman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Yazında, bizim çalışmamızdakine benzer şekilde depresif dönemde yürütücü işlev (8,33,34), sözel bellek (34,36), görsel bellek ve mekansal bellekte (36,37) bozulmalar bildirilmiştir. Bununla birlikte iyilik ve depresyon dönemindeki İUDB olan hastaları doğrudan karşılaştıran az sayıda çalışma vardır (38).…”
Section: Discussionunclassified
“…Hastalık dönemlerinin dışında, İUDB'nun iyilik dönemindeki hastalar üzerinde yapılan çalış-malarda da, hastaların bilişsel test sonuçlarının sağlıklı kontrollere göre bozulmuş olduğuna işaret edilmektedir (5,6,7,8,9,10). Ancak İUDB tanılı hastalarda bilişsel işlevlerle ilişkili araş-tırmaların sonuçları eşik altı belirtilerin varlığı dolayısıyla kafa karıştırıcıdır (9,11,12,13).…”
Section: Introductionunclassified